Tendencies, developments and steps toward inclusion in the education of Hungary - Simon, Katalin (Social Welfare: Interdisciplinary Approach, 2011)
The present study deals with certain milestones, key steps of education process in Hungary, which leads to a modern and democratic educational sector. The study keeps the public education segment in main focus, with outlooks to changes of vocational education and training, and to steps toward inclusion. Observing the process of education focusing on the individual, it is obvious that education holds a number of key tasks regarding the social welfare, in all of the life-stages of the individual.
Keywords: Hungary education system; competency based education methodology; VET; system of special education; integration